2010
DOI: 10.1186/1471-2458-10-345
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of the perceptions and information needs of public health inspectors responsible for food safety

Abstract: BackgroundIn Ontario, local public health inspectors play an important frontline role in protecting the public from foodborne illness. This study was an in-depth exploration of public health inspectors' perceptions of the key food safety issues in public health, and their opinions and needs with regards to food safety information resources.MethodsFour focus group discussions were conducted with public health inspectors from the Central West region of Ontario, Canada during June and July, 2008. A questioning ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 4 publications
(3 reference statements)
2
29
0
Order By: Relevance
“…Faced with requests for reassurance and information by increasingly demanding consumers, European and domestic public entities have responded by passing legislation such as the standards pertaining to product traceability and labelling (Savov & Kouzmanov, 2009). In order to guarantee the quality and safety of products, a variety of international regulations have been introduced, including ISO 9001 (International Organization for Standardization) standards, defining the requirements which a quality system needs to have in place in order to ensure control throughout the production process and prevent or detect any non-conformities; as regards operational tools there is the HACCP (Hazard Analysis Critical Control Points) system, whose purpose is to achieve self-checking objectives (Pham, Jones, Sargeant, Marshall, & Dewey, 2010;Ramphal & Simelane, 2010;Savov & Kouzmanov, 2009;Swinnen & Vandemoortele, 2009).…”
Section: Food Quality and Food Safetymentioning
confidence: 99%
“…Faced with requests for reassurance and information by increasingly demanding consumers, European and domestic public entities have responded by passing legislation such as the standards pertaining to product traceability and labelling (Savov & Kouzmanov, 2009). In order to guarantee the quality and safety of products, a variety of international regulations have been introduced, including ISO 9001 (International Organization for Standardization) standards, defining the requirements which a quality system needs to have in place in order to ensure control throughout the production process and prevent or detect any non-conformities; as regards operational tools there is the HACCP (Hazard Analysis Critical Control Points) system, whose purpose is to achieve self-checking objectives (Pham, Jones, Sargeant, Marshall, & Dewey, 2010;Ramphal & Simelane, 2010;Savov & Kouzmanov, 2009;Swinnen & Vandemoortele, 2009).…”
Section: Food Quality and Food Safetymentioning
confidence: 99%
“…Thus, salt and spices must be industrial applied during chilling storing phase for 2 h prior to meat or poultry cooking. Also, adding natural and lemon juice with salt concentration up to 7% of bacteriostatic action (Pham et al, 2010). However, C. jejuni polluted fast meat meals or chickens reflect either initial bacterial contamination or improper application of naturals and spices all through chilling store phase (Coker et al, 2002;Mauer et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Criteria included varied work structures, professional experience and seniority, and different levels of governments (17)(18)(19) . Environmental health officers were sought in three jurisdictions in Australia (New South Wales (NSW), Australian Capital Territory (ACT) and Queensland (QLD)) to provide a range of work structures.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that officers are comfortable with their role and knowledge regulating food safety (18) . *Corresponding author: Email deannecp@uow.edu.au r The Authors 2013…”
mentioning
confidence: 99%